Dirty Workers' Management of Hidden Emotions: Selling Intimacy and Seeking Social Support through the Shroud of Secrecy. (28th February 2018) - Wolfe, Anna Wiederhold; Blithe, Sarah Jane; Mohr, Breanna
Abstract: Through a qualitative analysis of legal prostitutes' emotional experiences, we examine how practices of secrecy inform emotion management and support-seeking behaviors. Our findings suggest that concealment practices serve protective functions, contributing to the construction of distinct occupational and social identity roles, avoidance of dirty work stigma, and protection of clients' definition of the situation. However, we also find that dirty workers tend to occupy a tensional space between revelation and concealment, especially when managing difficult emotions related to hidden identity roles. Our analysis suggests that resources available for managing emotions are inextricably linked to interactional role performances, and dirty workers may violate secrecy norms to attain levels of intimacy and social support contingent upon shared knowledge of salient social roles.